The Effect of Garlic Powder on Enterobius vermicularis infection - AL-BAYATI, Ahmed Fu'ad; AL-NAJAR, sabah Abbas (Journal of the Faculty of Medicine Baghdad, 2005)
Summary:Background: Enterobius vermicularis causes infection in different age groups , but specially in small ages . It is well known that parasitic infection in most middle eastern countries is common among them is Entrobius vermicularis , in which 11% is in school- children & 14% in pre-school children . In Iraq several studies on the prevalence of Enterobiasis in different age groups & from different areas were reported.Aim of study: This study was conducted to look for the therapeutic efficacy of garlic powder against Enterobiasis and the recurrence of this infection in many individuals to be compared with the drugs of choice that is a single dose, 100 mg of mebendazole tablets.Patients